2015
DOI: 10.1186/s12974-015-0432-3
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of Abcc8 or inhibition of newly upregulated Sur1-Trpm4 reduce inflammation and disease progression in experimental autoimmune encephalomyelitis

Abstract: BackgroundIn experimental autoimmune encephalomyelitis (EAE), deletion of transient receptor potential melastatin 4 (Trpm4) and administration of glibenclamide were found to ameliorate disease progression, prompting speculation that glibenclamide acts by directly inhibiting Trpm4. We hypothesized that in EAE, Trpm4 upregulation is accompanied by upregulation of sulfonylurea receptor 1 (Sur1) to form Sur1-Trpm4 channels, which are highly sensitive to glibenclamide, and that Sur1-Trpm4 channels are required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 51 publications
6
75
0
Order By: Relevance
“…Excessive activation of TRPM4 is associated with various non-malignant disorders and has been proposed to be a putative target for inhibition in numerous cardiovascular disorders and hypertension, [45][46][47][48][49] oxidative stress-mediated inflammatory diseases 10 and multiple sclerosis. 50 Trpm4 À/À mice were shown to be viable and fertile without obvious anatomical abnormalities, 51 TRPM4-selective inhibitor 9-phenanthrol We demonstrated that TRPM4-positive DLBCL patients treated with R-CHOP exhibited significantly worse survival, consistent with its expression being associated with adverse clinical parameters. One of the potential explanations for this observation might be attributable to TRPM4 activities that inhibit extracellular Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Excessive activation of TRPM4 is associated with various non-malignant disorders and has been proposed to be a putative target for inhibition in numerous cardiovascular disorders and hypertension, [45][46][47][48][49] oxidative stress-mediated inflammatory diseases 10 and multiple sclerosis. 50 Trpm4 À/À mice were shown to be viable and fertile without obvious anatomical abnormalities, 51 TRPM4-selective inhibitor 9-phenanthrol We demonstrated that TRPM4-positive DLBCL patients treated with R-CHOP exhibited significantly worse survival, consistent with its expression being associated with adverse clinical parameters. One of the potential explanations for this observation might be attributable to TRPM4 activities that inhibit extracellular Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 90%
“…Excessive activation of TRPM4 is associated with various non‐malignant disorders and has been proposed to be a putative target for inhibition in numerous cardiovascular disorders and hypertension, oxidative stress‐mediated inflammatory diseases and multiple sclerosis . Trpm4 −/− mice were shown to be viable and fertile without obvious anatomical abnormalities, TRPM4‐selective inhibitor 9‐phenanthrol exerted cardioprotective effects, while the Human Protein Atlas consortium included TRPM4 as one of the 1054 potentially druggable proteins of the human proteome, indicating that TRPM4 represents a potential experimental target.…”
Section: Discussionmentioning
confidence: 99%
“…Once it has been overactivated upon ischemia, hypoxia, trauma, or inflammation, the SUR1‐TRPM4 channel could cause unchecked influx of extracellular sodium and water, leading to consequential cell swelling, cell death, release of inflammatory cytokines, and breakdown of the blood–brain barrier 10, 11, 12, 13. GBC is well documented to bind to the SUR1 subunit and increase the probability of long closed states of the TRPM4 channel,16, 19, 34 without altering their structural expressions 20. Consistent with our previous data,20 we showed paralleled upregulations of SUR1 and TRPM4 after ACA/CPR.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, GBC has been proved to be neuroprotective in several disease models, including cerebral infraction, traumatic brain injury, subarachnoid hemorrhage, hemorrhagic encephalopathy of prematurity, spinal cord injury, hepatic encephalopathy, and multiple sclerosis 10, 11, 12, 13, 14, 15, 16. Moreover, the use of sulfonylureas (to treat diabetes) around the time of acute ischemic stroke has been associated with less neurological deficit and lower risk of hemorrhagic conversion 17, 18.…”
Section: Introductionmentioning
confidence: 99%
“…The sections were imaged using a CTR6500 confocal microscope equipped with Leica LAS AF software (Leica). Bielschowsky's staining was performed using the Bielschowsky OptimStain Kit as described (Hitobiotec Corp.) (57).…”
Section: Methodsmentioning
confidence: 99%